Innovation, Technology and Knowledge. - Karlsson, Charlie (Studies in global competition., 2011)
In the last four decades the developed economies have developed into veritable knowledge economies at the same time as more and more economies have entered the road to economic development. Typical for the developments during this time has been substantially increased investments in research and development (R & D) to generate new knowledge and new technologies and increased investments in diffusing existing knowledge by means of education and thereby raising the volume of human capital. However, many member states and regions within the EU are struggling with their economic development. This bo.